Cycleability as a Tool for Urban Resilience: A Multidimensional Diagnosis for Extreme Climate Events in the Global South - Melo, Ricardo Henryque Reginato Quevedo; Domeneghini , Jennifer; Silveira, André Luiz Lopes da; Melo, Rodrigo Henryque Reginato Quevedo (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study aims to demonstrate how cycleability can contribute to mitigating the impacts of extreme climate events, especially in Global South cities, by applying a diagnostic model based on focus areas as a tool to evaluate cycling infrastructure as a strategy for urban resilience. Methodology – The research adopts a systematic literature review and structures sustainable indicators across four focus areas: health, safety, emissions, and accessibility. These indicators were applied in a case study in the city of Porto Alegre, using quantitative and multitemporal analysis based on geospatial and technical data. Originality/relevance – The study addresses a key theoretical gap by positioning micromobility as an adaptive tool to climate change, highlighting integrated approaches applicable to vulnerable urban contexts. It introduces a novel interpretation of cycleability as a structural component of urban resilience. Results – The findings show that cycling infrastructure, when planned with multidimensional indicators, generates positive impacts on public health, reduces emissions, and improves urban accessibility, acting as a low-cost, high-effectiveness infrastructure in the face of climate crises. Theoretical/methodological contributions – The research presents a replicable methodology based on parametrizable indicators, enabling the diagnosis of cycling infrastructure’s contribution to urban resilience across different contexts. The simplified model enhances its practical application in public policy. Social and environmental contributions – The study reinforces the role of bike lanes as instruments of inclusion, health, and sustainability, promoting safer and more accessible cities prepared to face extreme events such as floods and heatwaves, while addressing the negative effects of car-centric models.